2013
DOI: 10.1186/1471-2458-13-104
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic experiences and mental health consequences among child survivors of the 2008 Sichuan earthquake: a community-based follow-up study

Abstract: BackgroundThe study was implemented to examine the relationship between traumatic experiences and longitudinal development of mental health for children and adolescents who survived the 2008 Sichuan earthquake.MethodsUsing the method of multistage systematic sampling, 596 children aged between 8 and 16 years were randomly selected from severely affected areas of the earthquake. These children were interviewed with standardized instruments of posttraumatic stress disorder (PTSD) and depression at the 15th month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 30 publications
4
48
1
2
Order By: Relevance
“…Most previous studies have shown that psychological morbidity decreases over time following natural disasters (Eksi & Braun, 2009; Fan et al, 2015; Piyasil et al, 2011), as also shown in our previous study on adults from the same data collection (Hlodversdottir et al, 2016), while other studies do not show significant changes over time (Jia et al, 2013; Thienkrua et al, 2006; Weems et al, 2010) or they show an increase in symptoms (Shaw et al, 1996; Ye et al, 2014). One reason for our findings might be that proper surveillance and psychological support was not implemented immediately for children after the eruption, indicating that children are a particularly vulnerable group that need developmentally appropriate interventions beyond the needs of adults.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Most previous studies have shown that psychological morbidity decreases over time following natural disasters (Eksi & Braun, 2009; Fan et al, 2015; Piyasil et al, 2011), as also shown in our previous study on adults from the same data collection (Hlodversdottir et al, 2016), while other studies do not show significant changes over time (Jia et al, 2013; Thienkrua et al, 2006; Weems et al, 2010) or they show an increase in symptoms (Shaw et al, 1996; Ye et al, 2014). One reason for our findings might be that proper surveillance and psychological support was not implemented immediately for children after the eruption, indicating that children are a particularly vulnerable group that need developmentally appropriate interventions beyond the needs of adults.…”
Section: Discussionsupporting
confidence: 80%
“…Usually, psychological symptoms peak during the first year post-disaster (Eksi & Braun, 2009; Fan, Long, Zhou, Zheng, & Liu, 2015; Piyasil et al, 2011), but some studies indicate that symptoms do not significantly decrease over time (Jia et al, 2013; Thienkrua et al, 2006; Weems et al, 2010). Long-term studies have even found an increase in psychological symptoms years after the disaster (Shaw, Applegate, & Schorr, 1996; Ye, Fan, Li, & Han, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Six events were studied in the 10 included studies: three earthquakes, one tsunami, one hurricane, and one wildfire. The earliest event was the Ash Wednesday fires in Australia in 1983(McFarlane & Hooff, 2009, and the latest was Sichuan earthquake in China in 2008 (Jia et al, 2013). Three of the studies followed the Spitak earthquake in Armenia in 1988, and another three followed South Asia tsunami in 2004.…”
Section: Overview Of the Included Studiesmentioning
confidence: 99%
“…With respect to study design, four of the 10 studies were cohort studies (Goenjian, Walling, Steinberg, Karayan, & Pynoos, 2005;Jia et al, 2013;Kronenberg et al, 2010;Najarian, et al, 2011), another four were cross-sectional studies (Agustini, Asniar, & Matsuo, 2011;Goenjian et al, 2009;Kilic, Kilic, & Yilmaz, 2008;McFarlane & Hooff, 2009), one was a descriptive study (Piyasil et al, 2011), and the other study was based on a case-series design (Ularntinon et al, 2008). One of the cohort studies compared PTSD symptoms between the subjects who had and had not received group/individual psychotherapy .…”
Section: Overview Of the Included Studiesmentioning
confidence: 99%
“…Kejadian letusan Gunung Kelud merupakan peristiwa yang sangat menegangkan dan membuat seluruh warga yang berdomisili di lereng gunung merasa kepanikan yang luar biasa. Hasil penelitian Jia et al (2013 ) mengatakan bahwa bukan hanya kerusakan secara fisik, namun banyak keluarga yang kehilangan sanak-saudaranya. Kehilangan orang-orang yang dicintai dan harta benda akan menjadi sebuah tekanan psikologis bagi warga yang terdampak letusan gunung kelud sehingga dapat menyebabkan munculnya post traumatic stress disorder (PTSD).…”
Section: Merasa Dalam Kondisi Terpurukunclassified